Sistem Monitoring Kelembapan Tanah, Suhu, pH dan Penyiraman Otomatis Pada Tanaman Tomat Berbasis Internet of Things - Rudy Gunawan; Tegas Andhika; Sandi .; Fadil Hibatulloh (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2019)
Diera Digitizing today almost all equipment uses technology. One benefit can be applied to agriculture, namely the internet, from things to monitor agricultural ecosystems and can be used as a reference for farmers in making decisions. This system is designed so that farmers can know the parameters of determining soil membranes, temperature, pH and watering and liquid fertilization are used to influence the growth of tomato plants, and facilitate farmers in relation, implementing this system can minimize crop recovery caused by weather factors, reduce nutrition , etc. Through the implementation of this support system, farmers are expected to produce tomatoes that are better and more suitable for consumption by the community. System testing and placement is carried out in a greenhouse where in several measurement parameters such as in the air and pH must be in accordance with the ideal level of tomato plant data, the optimal data level is between 60% -80% so it is not too dry for water, 24- 28 degrees Celsius, and pH is stable 5-6. The results of the humidity sensor readings showed good results considering the average error of 1.19%, the pH sensor with the linear regression calibration method with the equation to find the pH namely X (pH) = (330.46-Y (ADC)) / 45.49 the results obtained are quite accurate if the test error is 1.59%, while the temperature sensor tests the average error in the unit time test which is 0.92%. While testing the entire system obtained various results depending on the test obtained by the unit time for 24 hours, but tomato plants that have quite ideal results while those that are valued at 30% - 80% for soil moisture, and> 5.5 - 7.2 for pH . Keywords: Internet of things, monitoring, tomato plants, measurement parameters, greenhouse